Isolation of an allele of reeler by insertional mutagenesis. - Miao, G G (1994)
Reeler (rl) is an autosomal recessive mutation that affects migration of postmitotic neurons in the mouse central nervous system. The reeler (rl/rl) mouse displays a disruption of laminar structures in both the cerebellum and the forebrain and it exhibits tremors, dystonia, and ataxia. The molecular basis of the reeler phenotype is unknown because the gene involved has not yet been identified. We report here the isolation and characterization of an allele of rl, reelertransgene (rltg). This allele was generated by the fortuitous insertion of a transgene, supfos (sf), into the mouse rl locus. Crosses between rl/+ and rltg/+ mice yielded offspring that exhibited the reeler phenotype, indicating that rl and rltg are allelic. We cloned the genomic sequences flanking the transgene insertion site from the rltg/rltg mouse genome. Chromosomal mapping studies revealed that the 5' flanking cellular sequence maps to a locus, D5Gmr1, that lies in a region of mouse chromosome 5 that also contains the rl locus. Southern blot analysis using a probe derived from the D5Gmr1 locus revealed no gross structural rearrangement in the rl locus. Thus, unlike the two rl alleles described previously, rltg provides a molecular probe that can now be used to identify and isolate the rl gene.